The Size of the Esophageal Hiatus in Gastroesophageal Reflux Pathophysiology: Outcome of Intraoperative Measurements - GİRAL, ADNAN; YILDIZELİ, BEDRETTİN; EKİCİ, BÜLENT; BEKİROĞLU, GÜLNAZ NURAL; BATIREL, HASAN FEVZİ (SPRINGER, 2010)
The aim of the study was to investigate the impact of the size of the esophageal hiatus on lower esophageal sphincter pressure (LESP) and acid reflux. Patients with gastroesophageal reflux disease who underwent Nissen fundoplication in 2006-2008 were included. All underwent esophageal manometry and 22 had 24-h pH monitoring. The area of the esophageal hiatus was calculated from a photograph shot during surgery. A hiatal index was calculated via division of hiatal area with body mass index (BMI). Correlation and logistic regression analysis were performed. Twenty-eight patients (average age 44, 14 males) were enrolled. The mean BMI, LESP, DeMeester score, hiatal area, and hiatal index were 27 +/- 3.9 kg/m(2), 11.7 +/- 6.6 mmHg, 43 +/- 34, 3.83 +/- 1.24 cm(2), and 0.143 +/- 0.048, respectively. There was a significant negative correlation between hiatal area, hiatal index and LESP (-0.513, p = 0.005, r = -0.439, p = 0.019 respectively). Additionally there was a negative correlation between hiatal area and total LES length (r = -0.508, p = 0.013) and a significant positive correlation between hiatal area, hiatal index, and DeMeester scores (0.452, p = 0.035, 0.537, p = 0.01, respectively). Height and hiatal area were significant factors in multiple linear regression. The size of the esophageal hiatus significantly affects LESP and acid reflux, and hiatal index is a new value, which appears to reflect the amount of acid reflux. Total LES length is also shortened in patients with a large hiatus.
Keywords: Gastroesophageal reflux disease; Hiatal hernia; Esophageal hiatus; Intraoperative measurement; LAPAROSCOPIC ANTIREFLUX SURGERY; MESH-AUGMENTED HIATOPLASTY; HIGH-RESOLUTION MANOMETRY; ESOPHAGOGASTRIC JUNCTION; BARRETTS-ESOPHAGUS; HERNIA; SPHINCTER; DISEASE; PRESSURE; GERD